Lipid status and linear relationship between total cholesterol and triglycerides in glycogen storage disease type I - Zhang, Zhenjie; Yuan, Yuheng; Ma, M.-S.; Hong, Y.-H.; Sun, Z.-X.; Xu, Y.-W.; Wei, M.; Qiu, Z.-Q. (European review for medical and pharmacological sciences, 2020)
OBJECTIVE: Glycogen storage disease type la (GSDIa) is a glucose metabolic disorder. GSDIa patients are characterized by hypoglycemia, hepatomegaly, hyperlipidemia, and hyperlactacidemia. This retrospective study aimed to review the lipid status, explore lipid treatment targets, and assess preferable lipid-lowering drugs. PATIENTS AND METHODS: Clinical data on GSDIa patients' characteristics were collected. Most patients were followed-up once a year. Diet control and raw cornstarch treatment were used to maintain normal blood glucose and lipid levels. Some patients were given lipid-lowering drugs. We compared the lipid levels before and after each treatment. RESULTS: A total of 163 GSDIa patients were enrolled in this study. After treatment with raw cornstarch, the total triglycerides (TG) level has significantly decreased by 30 +/- 50% (8.37 +/- 7.23 to 5.39 +/- 5.29 mmol/L, p<0.001). There was no change in the total cholesterol (TC) level. Fifteen patients regularly took atorvastatin, and 15 took fibrates for more than one year. The therapeutic effect of atorvastatin was better than fibrates. The TC was positively correlated with TG after treatment, resulting in the following linear equation: TG=1.63xTC-2.86. Using this equation and Chinese children's normal TC level of 5.18 mmol/L, we aimed to maintain the patients at TG < 5.58 mmol/L. CONCLUSIONS: Patients with GSDIa have significant abnormalities in lipid metabolism. Because the complications of hyperlipidemia are caused mainly by TC, thereby, by maintaining it at a normal level, we could set a TG target by the linear equation that allowed a certain degree of hypertriglyceridemia. This study found that the therapeutic effect of atorvastatin was better than fibrates.
Gesehen am 13.01.2021